2021
DOI: 10.1155/2021/5514144
|View full text |Cite
|
Sign up to set email alerts
|

Risky Alcohol Use and Comorbidity in a Swedish Adolescent Emergency Psychiatric Inpatient Population

Abstract: Introduction. Underage drinking is associated with poor mental health. Early detection for risky alcohol use is recommended, although less implemented in adolescent care. The objective of this study was to investigate the prevalence of risky alcohol use and psychiatric comorbidity. Methods. Over a nine-month period, 145 eligible adolescents admitted to the child and adolescent emergency unit in Malmö, Sweden, were offered computerized screening with Alcohol Use Disorder Identification Test-Consumption (AUDIT-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…This was also found in the youngest group (17-29 years) of a national, general population survey used for comparison [14], although differences were not as pronounced as here. The same picture has been seen in adolescents in clinical treatment settings; despite the male predominance in alcohol-related diagnoses in the adult general population, these diagnostic entities in the present dataset were at least not more common in boys in child and adolescent emergency psychiatry [51].…”
Section: Discussionsupporting
confidence: 74%
“…This was also found in the youngest group (17-29 years) of a national, general population survey used for comparison [14], although differences were not as pronounced as here. The same picture has been seen in adolescents in clinical treatment settings; despite the male predominance in alcohol-related diagnoses in the adult general population, these diagnostic entities in the present dataset were at least not more common in boys in child and adolescent emergency psychiatry [51].…”
Section: Discussionsupporting
confidence: 74%
“…Saha et al [26] found a six-fold elevated risk for broadly defined mood disorder and drug dependence in depressed patients. Eberhard et al [27] describe a comorbidity of 41% of risky alcohol use and affective disorder in an emergency psychiatric inpatient population of adolescents. The link between MDD and SUD suggests a common pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Eberhard et al . [ 27 ] describe a comorbidity of 41% of risky alcohol use and affective disorder in an emergency psychiatric inpatient population of adolescents. The link between MDD and SUD suggests a common pathophysiology.…”
Section: Introductionmentioning
confidence: 99%